An ultra-capacitor-based current source for magnetic field demonstration - Meyn, Jan-Peter (European Journal of Physics, 2010)
An ultra-capacitor in parallel with the output of a dc power supply reduces the source resistance and yields an electrical current of up to 900A through a low resistance load. The magnetic field of wires is made visible with iron filings over a large area. © 2010 IOP Publishing Ltd.
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.PI.PDP.anultr